An Analysis of The Divine Principles of K.H. Abdullah Syafi’ie (1910-1985 M) - Muhammad Choirin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2020)
K.H. Abdullah Syafi’ie is widely known as an Islamic scholar and preacher in the Indonesian Muslim community, particularly among Betawi natives. His significant contribution to spreading Islam, notably in education, is depicted through as-Syafi’iyah Islamic Education. Furthermore, his role in Islam in the Indonesian archipelago is evidenced by writing more than twenty-one titles of books in the field of Islamic faith and Usuluddin, which has been marking his name in the Islamic discourse. This paper aims at exploring the persona of K.H. Abdullah Syafi'ie as a Muslim theologian, particularly in the issues related to the science of kalam. In doing so, this study employs historical approaches combined with interviews and observation. This study finds that the thought of divinity established within the literature written by KH Abdullah Syafi’ie supports the validity of ahli sunnah wal jama’ah Asy’ariyah belief which he had practiced.